AUDIT ENERGI AWAL MELALUI PERHITUNGAN INTENSITAS KONSUMSI ENERGI (IKE) LISTRIK (STUDI KASUS PADA GEDUNG POLITEKNIK MUARA TEWEH) - Juli Chandra Teruna (Jurusan Teknik Elektro, Fakultas Teknik, Universitas Borneo Tarakan, 2019)
An audit of electricity is evaluation of the utilization of energy and identification savings opportunities electricity energy as well as recommendations an incrase in the efficiency on users of energy source and users energy in order to conservation energy. Energy audit review of the condition and operation of equipment that uses electricity energy as well as instruments related to energy efficiency. Based on the result of research, the effective extensive Politektik Muara Teweh building is 615m2 with an average energy consumption is 2598 kWh each month while the consumption of electricity energy index amounted to 4,224 kWh/m2 each month or by 50,698 kWh/m2 each year with energy of bulding cost amounted to Rp. 902,47/kWh. Consumption of electricity energy of Politeknik Muara Teweh including very efficient criteria. This audit energy is expected to be identify opportunities for savings electricity energy consumption through energy audit detailed.